Dysbiosis of infant gut microbiota is related to the altered fatty acid composition of human milk from mothers with gestational diabetes mellitus: a prospective cohort study - Kelei Li; Jin Jin; Zhizuo Liu; Chuanjing Chen; Ludi Huang; Yongye Sun (Gut Microbes)
Gestational diabetes mellitus (GDM) is known to be associated with dysbiosis of offspring gut microbiota, but the mechanism remains unclear. The present prospective study explored the role of human milk fatty acid composition in this association. Mothers with GDM and normal controls were recruited at 24–28 gestational weeks. Follow-up was conducted at 1–3 days postpartum and 1 month postpartum to collect human milk and infant feces. A total of 80 mother-infant pairs (40 in the GDM group and 40 in the normal group) were included in the study. The mothers received guidance on diet and exercise but not drug therapy. All infants were exclusively breastfed. We observed significant differences in 8 phyla and 13 genera in the infant between GDM and normal groups at 1–3 days postpartum or 1 month postpartum. Among these bacteria, significant time × group interaction was observed for 7 phyla (such as Acidobacteriota, Gemmatimonadota, and Myxococcota) and 9 genera (such as Sphingomonas, Allorhizobium Neorhizobium Pararhizobium Rhizobium, and TM7a), after adjusting for confounding factors. Changes in these differential infant bacteria were negatively correlated with changes in C18:3n-3 and total n-3 PUFA levels of breast milk. The increases in C18:3n-3 and total n-3 PUFA levels in human milk over time were much greater in the normal group compared to the GDM group. Our findings indicate that altered human milk fatty acid composition is one important reason for GDM-related dysbiosis of offspring gut microbiota.